The Oxford Handbook of dance and ethnicity - Shay, Anthony 1936-; Sellers-Young, Barbara ca. 20./21.Jh (Oxford University Press, 2016)
"This compilation of 31essays from scholars throughout the globe examines the relationship between ethnicity as a signifier of identity and the dances associated with an ethnic designation. As such, it incorporates the critiques of previous designations of dance as folk, classical, etc. in favor of a more nuanced and complex view of ethnicity as at the intersection of race, gender, nation and life style"...
Includes bibliographical references and index
Keywords: Gesellschaft; Dance -- Anthropological aspects; Dance -- Social aspects; Ethnicity; Tanz; Ethnizität; Kulturelle Identität; Aufsatzsammlung